Thermal rounding exponent of the depinning transition of an elastic string in a random medium - Bustingorry, Sebastián (2012)
We study numerically thermal effects at the depinning transition of an elastic string driven in a two-dimensional uncorrelated disorder potential. The velocity of the string exactly at the sample critical force is shown to behave as V∼Tψ, with ψ the thermal rounding exponent. We show that the computed value of the thermal rounding exponent, ψ=0.15, is robust and accounts for the different scaling properties of several observables both in the steady state and in the transient relaxation to the steady state. In particular, we show the compatibility of the thermal rounding exponent with the scaling properties of the steady-state structure factor, the universal short-time dynamics of the transient velocity at the sample critical force, and the velocity scaling function describing the joint dependence of the steady-state velocity on the external drive and temperature.